Current status of schistosomiasis in school-aged children in Mwanga district, Tanzania: impact of two decades of annual Mass Drug Administration programme - Jeremia J. Pyuza; Brice Meulah; Pytsje T. Hoekstra; Noel Mdende; Elizabeth Mvilli; Lisette van Lieshout; Stan T. Hilt; Paul L. A. M. Corstjens; Maria Yazdanbakhsh; Sia E. Msuya; Govert J. van Dam (Parasitology)
Schistosomiasis is a neglected tropical disease with significant health implications, particularly among children. A cross-sectional study was conducted among school-aged children (SAC) in Mwanga district, Tanzania, a region known to be co-endemic for S. haematobium and S. mansoni infection and where annual mass drug administration (MDA) has been conducted for 20 years. In total, 576 SAC from 5 schools provided a urine sample for the detection of Schistosoma circulating anodic antigen using the upconverting particle-based lateral flow (UCP-LF CAA) test. Additionally, the potential of the point-of-care circulating cathodic antigen (POC-CCA) and microhaematuria dipstick test as field-applicable diagnostic alternatives for schistosomiasis were assessed and the prevalence outcome compared to UCP-LF CAA. Risk factors associated with schistosomiasis was assessed based on UCP-LF CAA. The UCP-LF CAA test revealed an overall schistosomiasis prevalence of 20.3%, compared to 65.3% based on a combination of POC-CCA and microhaematuria dipstick. No agreement was observed between the combined POC tests and UCP-LF CAA. Factors associated with schistosomiasis included age (5–10 years), involvement in fishing, farming, swimming activities and attending 2 of the 5 primary schools. Our findings suggest a significant progress in infection control in Mwanga district due to annual MDA, although not enough to interrupt transmission. Accurate diagnostics play a crucial role in monitoring intervention measures to effectively combat schistosomiasis.